Sistem Informasi Penjualan Beras Berbasis Website - Eni Pudjiarti; Dini Nurlaela; Wina Sulistyani (Universitas Bina Sarana Informatika, 2019)
Abstract: The rapid development of the technology world requires technology users to keep up with its development. For this reason, new innovations have emerged in various aspects of life to facilitate human work. Sales are one aspect that is also growing rapidly. One new innovation that emerges is E-commerce or internet-based sales. E-commerce helps connect between sellers and buyers of different places through cyberspace. With the existence of E-commerce human work becomes more effective and efficient, because it can be accessed anytime and anywhere without limitation of time and region. Website is widely used for making E-commerce based sales systems. The website contains pages that are deepened in the form of information in the form of text, images, audio, video and animation that can be accessed by the public. The website-based sales system is very suitable for the sale of rice, because rice is one the staple foods of the Indonesian people and there are still many sellers who sell their rice products manually. Keywords: Innovation, E-commerce, website, Rice Sales